2000
DOI: 10.1093/bja/85.5.708
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhage and risk factors associated with retrobulbar/peribulbar block: a prospective study in 1383 patients

Abstract: Patients undergoing intraocular surgery are elderly and may have disease or be receiving medication which increases the risk of haemorrhage. We interviewed 1383 consecutive patients scheduled for eye surgery requiring retrobulbar/peribulbar block about their use of non-steroidal anti-inflammatory drugs, oral steroids and warfarin. A history of diabetes mellitus and globe axial length was noted. Medial peribulbar and inferolateral retrobulbar blocks were performed by three specialists and six doctors in trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 18 publications
0
43
0
7
Order By: Relevance
“…The largest reported series involved 19 283 cataract operations, 6 which in common with other reports, did not identify an increased risk of haemorrhagic complications during local anaesthesia 6,7 or cataract surgery. 6,8,9 Other studies have reported an increased risk of minor haemorrhagic, but not visually threatening complications in patients taking warfarin.…”
Section: Introductionmentioning
confidence: 73%
“…The largest reported series involved 19 283 cataract operations, 6 which in common with other reports, did not identify an increased risk of haemorrhagic complications during local anaesthesia 6,7 or cataract surgery. 6,8,9 Other studies have reported an increased risk of minor haemorrhagic, but not visually threatening complications in patients taking warfarin.…”
Section: Introductionmentioning
confidence: 73%
“…Studies have concluded that both the intramuscular injection of ketorolac tromethamine and the use of diazepam, mefenamic acid and acetaminophen (alone or in combination with each other) are not effective in reducing pain perception. Only peribulbar block was effective in reducing pain for this procedure [13]. However, one should take into consideration the risk/benefit of this technique.…”
Section: Discussionmentioning
confidence: 92%
“…However, one should take into consideration the risk/benefit of this technique. The risks posed by these types of analgesia such as perforation of the eye, retrobulbar hemorrhage, traumatic optic neuropathy, central nervous system as well as cardiorespiratory depression have been reported complications of this form of anesthesia [13]. In addition to the risks of retrobulbar anesthesia, it induces akinesia making it a disadvantage when you need to direct the patient's eye movements during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Excision of lesions (nevi, keratosis, carcinomas) are frequently associated with minor bleedings but rarely (< 5%) major ones, and optimization of local hemostasis should generally suffice 58,59 . Cataract extraction is an avascular surgery usually done nowadays with phacoemulsion and topical anesthetics -retrobulbar anesthesia is rarely associated with significant bleeding in anticoagulated patients but this could mandate urgent decompression 60 . Minor bleeding (subconjuntival hemorrhage or dot hyphemas) without any vision loss may occur in up to 10 percent of patients but is not a reason for changing the anticoagulant regimen 61 .…”
Section: Warfarinmentioning
confidence: 99%